Disinformation and Democracy: Assessing the Threat of Fake News to Societal Trust, Security, and Global Competitiveness (Global Journal of Management and Business Research, 2025)
This paper explores the growing threat of fake news and disinformation in the digital era particularly in the European context It combines an extensive literature review with primary data from two online surveys conducted in Hungary focusing on media literacy perceived risk of misinformation and its influence on attitudes toward EU-level policies such as the European Green Deal The study reveals notable generational and educational disparities in media competence and public trust Findings indicate that frequent political news consumers are more likely to perceive fake news as a threat to climate policy and governance The paper concludes that misinformation poses not only a media problem but also a challenge to democratic institutions public health economic stability and societal cohesion requiring robust policy and educational responses
Keywords: fake news; disinformation; media literacy; european green deal; digital propaganda; hungary; public opinion; survey research